Strategy for Disclosure of Sustainability Reports for Companies Registered as Sharia Issuers in North Sumatra Province - Hayati, Isra; Asmuni (LPPM, Universitas Islam Syarifuddin Lumajang, 2025)
This study investigates the challenges, solutions, strategies, and Sustainability Report models among sharia-compliant companies listed in North Sumatra, Indonesia. Using a descriptive qualitative approach and Analytical Network Process (ANP) as the analytical tool, data were gathered from seven experts and practitioners through interviews and ANP questionnaires. Supplementary insights were drawn from national and international journal sources on sustainability reporting. The study identifies key problem areas with varying agreement levels: operational issues (53%), OJK-related challenges (36%), community concerns (26%), human resources (3%), and supervision (2%). Operational barriers include IT readiness, data availability, and lack of roadmaps. OJK issues focus on unclear policies, weak enforcement, and political influence. Proposed solutions include strengthening IT infrastructure (18%), improving HR competencies (14%), and enhancing supervision through sharia compliance and collaboration (79%). External solutions involve policy reform, data integration, and technical guidance by OJK (21%), alongside limited community-based strategies (2%). Strategically, the study recommends increased synergy between OJK, stakeholders, and global frameworks like GRI, as well as greater education and socialization efforts for sharia issuers. The findings contribute to the global discourse on sustainable finance by highlighting localized barriers and actionable solutions for advancing ESG practices in Islamic finance.